2017
DOI: 10.1088/2040-8986/aa7291
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of hydrogenated amorphous silicon solar cells with front-surface hexagonal plasmonic arrays from nanoscale lithography

Abstract: The study first uses numerical simulations of hexagonal triangle and sphere arrays to optimize the performance of hydrogenated amorphous silicon (a-Si:H) photovoltaic devices. The simulations indicated the potential for a sphere array to provide optical enhancement up to 7.4% compared to a standard cell using a nanosphere radius of 250nm and silver film thickness of 50nm. Next a detailed series of a-Si:H cells were fabricated and tested for quantum efficiency (QE) and characteristic and current-voltage (I-V) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…10 Solar spectrum data were obtained in accordance with ASTM G173 for use as standard parameters for the photovoltaic cells. 39,40 For the graphs and formulas used in calculation, refer to the Supporting Information. T vis /T sol is used primarily as a measure of the performance of a THM, and the theoretical maximum is 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Solar spectrum data were obtained in accordance with ASTM G173 for use as standard parameters for the photovoltaic cells. 39,40 For the graphs and formulas used in calculation, refer to the Supporting Information. T vis /T sol is used primarily as a measure of the performance of a THM, and the theoretical maximum is 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Values were calculated for parameters such as the figure of merit (Φ), integrated solar transmittance and reflectance ( T sol and R sol ), integrated visible transmittance (τ vis ), integrated IR reflectance ( R IR ), and integrated visible transmittance and reflectance ( T vis and R vis ), and T vis / T sol values were then calculated . Solar spectrum data were obtained in accordance with ASTM G173 for use as standard parameters for the photovoltaic cells. , For the graphs and formulas used in calculation, refer to the Supporting Information. T vis / T sol is used primarily as a measure of the performance of a THM, and the theoretical maximum is 2.…”
Section: Resultsmentioning
confidence: 99%
“…A thin metallic film with an array of subwavelength holes has been proposed before to improve the efficiency of organic solar cells [26]. However, the honeycomb pattern benefits from scalable and relatively low cost self-assembled nano-beads lithography technique [11,[27][28][29][30][31]. In [32], the authors used nano-beads lithography to make a perforated metallic film which in turn could be used to lower the resistance of the top contact.…”
Section: Plasmonic Thin Film A-si:h Solar Cellmentioning
confidence: 99%
“…Massoit and associates used one dimensional array of silver strips to form a broadband light trapping mechanism in order to enhance the light absorption of the cell [10]. Zhang et al, found improved a-Si:H PV device performance with an enhanced front-surface hexagonal plasmonic arrays made from nano-scale lithography [11]. These approaches are promising and this study aims to further those efforts by analyzing a new top contact that is able to be manufactured economically at a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…They are then ready to be used for any application (e.g. as a mask for plasmonic enhancement of photovoltaic devices [26] ).
Fig.
…”
Section: Close-packed Sphere Lithographymentioning
confidence: 99%